Problems of maize cultivation and the role and approach of local farmers in solving this problem - Aryal, Sri Hari Prassed (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
Maize is the main crop in this village in Ihe Gulmi district of Nepal. Farmers from this village discuss their experiences participating in maize-improvement research with Ihe Local Initiatives for biodiversity Research and Development (U-SIRO). The farmers preferred their traditional variety for its flavor and fodder, but it tended to fall. This paper describes how they worked with U-SI RO on maintaining Ihe characteristics they preferred in their traditional maize variety, while working lo overcome the problem of its weak stems.